2017
DOI: 10.1002/ijgo.12211
|View full text |Cite
|
Sign up to set email alerts
|

The role of men in induced abortion decision making in an urban area of the Philippines

Abstract: Objective To understand beliefs about unintended pregnancy and abortion, and perceptions about male roles related to pregnancy decision-making among men in the Philippines. Methods Qualitative data were collected during in-depth interviews and focus group discussions with men in an urban area of the Philippines between October 2007 and July 2008. Interview participants were purposively sampled from a local survey based on their having reported being “afraid or troubled” or “afraid and planned to terminate” i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…Lastly, young parents very much valued and depended on the acceptance and support of their family and friends, especially when their relationships with their partners dissolved. This is consistent with studies with Filipino youth which found that partner and family support were important determinants of whether unintended pregnancy resulted in birth or induced abortion [78,79].…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, young parents very much valued and depended on the acceptance and support of their family and friends, especially when their relationships with their partners dissolved. This is consistent with studies with Filipino youth which found that partner and family support were important determinants of whether unintended pregnancy resulted in birth or induced abortion [78,79].…”
Section: Discussionsupporting
confidence: 90%
“…Disclosure is a critical component of an abortion-related care trajectory, as it can impact whether and how a woman is able to obtain an abortion. 8 With the exception of a study of young men in the Philippines, 41 all evidence on the experience of disclosure was from women who had sought abortions, or studies where men were a secondary sample of interest. Women who had either sought abortion care or post-abortion care at a facility in Lusaka, Zambia, reported that the fear of disclosure also included fear of partner interference in the pregnancy or abortion decision, and fear of repercussions from fathers.…”
Section: Resultsmentioning
confidence: 99%
“…(2017) [18] EmBase Ovid Medline (R) without Revisions Qualitative 15 men living in urban areas in the Philippines…”
Section: Qualitativementioning
confidence: 99%
“…Men who desire to validate a decision related to an induced abortion were clouded ~ 28 ~ by their societal expectations as men and fathers in a family and avoid any "sin" associated with carrying out such an occurrence. It was also found out that women partners of males seeking an induced abortion led to men experiencing complications in their relationships such as physical and emotional separations because these men prefer to avoid committing the "sin" associated with induced abortion (Hirz et al, 2017) [18] . Men tend to experience both positive and painful feelings four months after the loss.…”
Section: Abortionmentioning
confidence: 99%